2006
DOI: 10.1007/s00464-005-0621-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic and open tension-free repair of recurrent inguinal hernias: a prospective randomized study

Abstract: Laparoscopic inguinal hernia repair (TAPP or TEP) is the method of choice for dealing with recurrent inguinal hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
113
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 28 publications
7
113
1
3
Order By: Relevance
“…Our study has shown that operation time is shorter in the Lichtenstein group (59.6 6 9.9 minutes) than in the TAPP group (64.4 6 8.4 minutes), although because of the small sample size, this trend did not reach a statistical significance (P 5 0.068). Our data are similar to the data from several other investigations, 15,19,25 although Eklund et al 16 found no difference in the operation time between the laparoscopic and Lichtenstein methods.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study has shown that operation time is shorter in the Lichtenstein group (59.6 6 9.9 minutes) than in the TAPP group (64.4 6 8.4 minutes), although because of the small sample size, this trend did not reach a statistical significance (P 5 0.068). Our data are similar to the data from several other investigations, 15,19,25 although Eklund et al 16 found no difference in the operation time between the laparoscopic and Lichtenstein methods.…”
Section: Discussionsupporting
confidence: 92%
“…The same advantages of the laparoscopic method in comparison with the Lichtenstein approach are documented also by other authors. [14][15][16]19,25 There were no differences found in the total number of early complications between the open and laparoscopic methods (33.3% versus 14.3% for TAPP and Lichtenstein, respectively; P 5 0.19). Authors of some previous studies have shown that laparoscopic methods are characterized by fewer postoperative complications than Lichtenstein operations.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The meta-analysis by Pisanu (8) contained the largest number of exclusively prospective randomized trials (RCTs) (11,12,13,14,15,16,17). All the RCTs included in that meta-analysis compared the laparo-endoscopic procedures with the open Lichtenstein technique.…”
mentioning
confidence: 99%